The Epistemological Errors in Regulation of Absolute Competence on Mortgage Disputes in Credit Contracts - Ade Saptomo; Rocky Marbun; Anis Mashdurohatun (UNISSULA, 2023)
The development of Collateral Law relating to the attachment of Mortgage Rights to a Credit Agreement, nowadays, it is impossible to avoid the development of Sharia Law in Indonesia. This study tries to reveal an epistemological error from the Supreme Court which issued Supreme Court Regulation Number 14 of 2016 concerning Procedures for Settlement of Sharia Economic Cases against the phenomenon of disparity in judicial decisions on Mortgage attached to Sharia-based Credit Agreements. This study uses a normative juridical method using the Communication Speech Act approach and the Relationship Trichotomy approach. The results of this study indicate that there was an epistemological error from the Supreme Court which issued the Supreme Court Regulation Number 14 of 2016, instead of as a form of resolving legal anomalies, which showed the existence of domination based on power and authority from the Supreme Court by applying an eclecticism mechanism to rights. Dependents with Sharia-based Credit Agreements which are assumed to be true.